(untitled) (Fiep Bulletin - online, 2025)
Introduction: This study analyzes the effect of Intermanual Transfer of Learning (IMTL) in participants of extension projects at the Federal University of Acre, aiming to understand the mechanisms of motor control at different levels of the nervous and neuromuscular systems. Understanding these processes is relevant to health and sports sciences, providing insights to optimize motor learning and rehabilitation. Objective: To analyze the effect of IMTL on global manual dexterity (GMD) in individuals with different hand preferences, considering variables such as sex and age group. Methods: This is a cross-sectional, descriptive and comparative study carried out with 196 volunteers of both sexes, aged between 6 and 57 years, classified as right-handed (R) or left-handed (L). Participants were divided into five age groups: Group 1 (late childhood), Group 2 (preadolescence), Group 3 (post-puberty), Group 4 (young adult) and Group 5 (middle age). Handedness preference (Hp) was assessed using the Dutch Handedness Questionnaire, and IMTL was measured using the Box and Blocks Test, which assesses GMD. Results:The results showed no statistically significant differences in Hp relative to MP (p = 0.353). However, significant effects were observed for sex (p = 0.021) and age (p = 0.002). Conclusion: IMTL was found to be similar between right- and left-handed individuals, higher in males, and showed the largest differences between late childhood and middle age, indicating a progressive decline in intermanual transfer across age groups.